New Trends in Health Tourism Development of Ivano-Frankivsk Region in Ukraine - Hladkyi, Oleksandr; Tkachenko, Tetiana; Shparaga, Tetiana; Kulivnuk, Volodymyr (Anais Brasileiros de Estudos Turísticos, 2022)
The article discusses essence and new trends of health tourism development in Ivano-Frankivsk region of Ukraine. Literature review is based on comprehensive analysis of Ukrainian and European scientific investigations connected with problems of health treatment, medical and rehabilitation studies as well as with health improvement via tourism. The different types of health tourism as well as the difference between wellness tourism and medical tourism are disclosed. The wide characteristic of health tourism potential in Ivano-Frankivsk region of Ukraine is proposed. The comprehensive analysis of health tourism development in Ivano-Frankivsk region is highlighted. The dynamics of tourism attendance in Ivano-Frankivsk region as well as the number of tourists served by tour operators and travel agents in this region are defined. The dynamics of tourist tax revenues in Ivano-Frankivsk region and different types of tourist activities in the Ivano-Frankivsk region are explored. The number of tourists who visited the Ivano-Frankivsk region for health tourism is calculated. The number of sanatoriums, health resorts, medical and health facilities of Ivano-Frankivsk region are revealed.